(untitled) (Bangladesh Journal of Plant Taxonomy, 2006)
A taxonomic account of six species of Pleurocarpous mosses of Bangladesh of the families Symphyodontaceae and Amblystegiaceae under the order Hookeriales and Hypnobryales respectively are given. Key words: Pleurocarpous moss, Hookeriales, Hypnobryales, Symphyodontaceae, Amblystegiaceae, Bangladesh DOI: 10.3329/bjpt.v13i1.591 Bangladesh J. Plant Taxon. 13(1): 29-40, 2006 (June)